Government Capacity in` Recovering Tourism Sector in the Pandemic Period - Slamet Rosyadi (Insignia: Journal of International Relations, 2021)
The Covid-19 pandemic reduced national income in the tourism sector. Government capacity is needed to overcome these problems. Using comparisons between Indonesia and Thailand, this study aims to test the government's capacity to restore the tourism sector during a pandemic. This comparison is necessary in order to obtain an in-depth analysis of the capacity of governments representing ASEAN in the recovery of the tourism sector. The literature study method and secondary data were used in this research. The data analysis used a qualitative descriptive approach. The results of the study found that the governments in both countries had sufficient capacity to restore the tourism sector due to the Covid-19 outbreak. However, the capacity of the Thai government is somewhat better in integrating tourism recovery efforts and preventing the transmission of Covid-19. However, bribery and corruption are found in Thailand. This study concludes that the recovery of the tourism sector during a pandemic requires the capacity of the government to provide a number of economic stimulus packages that are integrated with regulatory health and quarantine protocols.